THE HYPHOMYCETE GENUS DACTYLARIA SACC. - MIEN A. RIFAI (REINWARDTIA, 1968)
An emended delimitation of the genus Dactylaria Sacc. is proposed and the two accepted species, which are non-predaceous and dematiaceous, are redescribed and illustrated. The affinity of many nematode-trapping species currently classified in Dactylaria with the didymosporous genera Arthrobotrys Corda, Candelabrella Rifai & R. C. Cooke and Genicularia, Rifai & R. C. Cooke is discussed and the scopes of the latter genera are enlarged, and consequently several new combinations are made.